QUASI-ANHARMONIC ANALYSIS REVEALS INTERMEDIATE STATES IN THE NUCLEAR CO-ACTIVATOR RECEPTOR BINDING DOMAIN ENSEMBLE - BURGER, VIRGINIA M. (Pac Symp Biocomput, 2012)
The molten globule nuclear receptor co-activator binding domain (NCBD) of CREB binding protein (CBP) selectively recruits transcription co-activators (TCAs) during the formation of the transcription preinitiation complex. NCBD:TCA interactions have been implicated in several cancers, however, the mechanisms of NCBD:TCA recognition remain uncharacterized. NCBD:TCA intermolecular recognition has challenged traditional investigation as both NCBD and several of its corresponding TCAs are intrinsically disordered. Using 40µs of explicit solvent molecular dynamics simulations, we relate the conformational diversity of ligand-free NCBD to its bound configurations. We introduce two novel techniques to quantify the conformational heterogeneity of ligand-free NCBD, dihedral quasi-anharmonic analysis (dQAA) and hierarchical graph-based diffusive clustering. With this integrated approach we find that three of four ligand-bound states are natively accessible to the ligand-free NCBD simulations with root-mean squared deviation (RMSD) less than 2Å. These conformations are accessible via diverse pathways while a rate-limiting barrier must be crossed in order to access the fourth bound state.